Implementering av Rätt metod gallring och Rätt metod planering - en uppföljning i fält inför fortsatt utvecklingsarbete - Ekelund, Fredrik (SLU/School for Forest Management, 2019)
Ground damages due to the use of heavy machinery in the Swedish forestry is legislated in the Forestry Act where a minimum of demands for the forestry is set. To further strengthen the consideration to environmental aspects in the forestry, for example the importance of protecting certain soil types and waterways, FSC and PEFC certification are implemented.